2015
DOI: 10.3329/bjp.v10i1.21329
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective activity of fruits of <i>Sechium edule</i>

Abstract: The present work deals with the study of the ethanolic extract of fruits of Sechium edule for cardioprotective activity. Cardioprotective activity of the ethanolic extract of fruits of S. edule was determined by the administration of isoproterenol (60 mg/kg, s.c) for two days. Pretreatment with S. edule (200 mg/kg, p.o and 100 mg/kg, p.o) for 28 days in significantly (p<0.01) reduce the levels of serum transaminases, alkaline phosphates, lactate dehydrogenase, creatinine kinase, total cholesterol, triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Chayote extract using ethanol solvent contains alkaloids, flavonoids, glycosides, sapaonins, tannins and triperten (Siahaan, 2020). This study is in line with Neeraja et al (2015), that the ethanol extract 200 mg/KgBW can significantly increase HDL.…”
Section: Resultssupporting
confidence: 91%
“…Chayote extract using ethanol solvent contains alkaloids, flavonoids, glycosides, sapaonins, tannins and triperten (Siahaan, 2020). This study is in line with Neeraja et al (2015), that the ethanol extract 200 mg/KgBW can significantly increase HDL.…”
Section: Resultssupporting
confidence: 91%
“…The cardioprotective activity of the ethanolic extract of fruit was also determined in animal models. Results showed that Wistar rats treated with chayote fruit extract for 28 days significantly (p <0.01) reduced the serum levels of several enzymes (SGOT, SGPT, ALP, LDH, CK), total cholesterol, triglycerides, LDLcholesterol, VLDL-cholesterol, and increased the levels of HDL-cholesterol(Neeraja, Debnath, & Firdous, 2015). The angiotensin-converting enzyme (ACE) inhibitor nicotianamine was purified from chayote, however, its absorption and efficacy on reninangiotensin-aldosterone system was not highlighted(Hayashi, Nakayama, Aoyagi, 6.3.…”
mentioning
confidence: 97%
“…The product hence obtained was reduced to a dark-colored mass by keeping in a boiling water bath for further solvent elimination. The obtained hydroalcoholic extract was preserved in a refrigerator (4°C) until further use [ 16 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…extract was found to reduce the level of malondialdehyde [ 17 ]. A literature survey also revealed the cardioprotective property [ 19 ] of this fruit. Additionally, it has been demonstrated that the polyphenolic extract of S.E.…”
Section: Introductionmentioning
confidence: 99%